PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN (Studi Kasus pada PT. GO-JEK) (Jurnal Ekobis : Ekonomi Bisnis & Manajemen, 2020)
Customer satisfaction at PT. GO-JEK does not decrease or increase every year, this is due to strategies that continue to strive to always be able to satisfy their customers. This research was conducted to find empirical evidence of the effect of price and service quality on customer satisfaction at PT. GO-JEK in the area around Tebet.Determination of the results of this sample using the Lemeshow formula, from the formula obtained as many as 74 respondents and taken by area (cluser) sampling (sampling by region). Data analysis techniques in the study using multiple regression analysis with the program used was SPSS version 17.00.The results of this study indicate that all hypotheses can be accepted, 1) there is a positive and significant effect between price on customer satisfaction acceptable. 2) There is a positive and significant effect on service quality on customer satisfaction can be accepted. Price is the most influential variable on customer satisfaction of PT. GO-JEK.